KEPUASAN KERJA PERAWAT DI RUMAH SAKIT CIAMIS - Endrian Mulyady Waluyo; Hani Septiani; Aldi Fajar Nugraha (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2022)
Nurse job satisfaction has a significant effect on nurse performance. To have good job satisfaction, nurses must have high motivation, in addition to these factors, maintenance factors also need to be considered. So job satisfaction becomes an important element for hospitals to improve maximum service. If there is dissatisfaction, it will cause the nurse to leave. The purpose of this study was to describe the job satisfaction of civil servants and non civil servants at RSUD Ciamis. The research method uses a descriptive method that explains one variable, the data collection process uses a questionnaire sheet filled out by the respondent. The population in this study amounted to 407 nurses working in Ciamis Hospital with 151 civil servant nurses staffing status and 256 non-civil servants nurses, with the minimum number of samples used by researchers amounted to 38 samples, this sample size was obtained by using the G power calculation. The results showed that 3 respondents were satisfied with civil servant nurses and 7 respondents were not satisfied. While the noncivil servant respondents who are satisfied are 16 respondents and those who are not satisfied are 12 respondents. The study showed that nurses' dissatisfaction was experienced by 70% of Civil Servants, while 42.9% of non-civil servants are satisfied with the job.